And Now, Please Sign on the Dotted Line: Teaching Residents About Professional Life After Residency. Issue 5 (May 2018) - Salib, Sherine; Valencia, Victoria; Moreno, Alejandro
Abstract: Objectives: Despite possible long-term repercussions, few training programs teach their residents about the business of medicine. In particular, certain contractual issues can adversely affect a young physician's career mobility. Methods: We designed a business-of-medicine curriculum and used a survey to determine whether the curriculum satisfied attendees' perceived knowledge gaps about the topics covered in the course, which included four key contractual matters: physician employment contracts (including restrictive covenants), malpractice insurance, job search, and interviewing skills. We used a postsurvey in 2015 and added a presurvey for the course in 2016. The same content was delivered in a 1-hour conference to internal medicine residents attending a regular noon conference series in 2015 and a regional academic meeting in 2016. Survey data are presented in terms of descriptive statistics. We used χ 2 tests for comparisons of pre- and post-Likert scale survey data. Results: Of 108 residents, 50 returned the surveys for an overall response rate of 46% across the 2 years of the course. Overwhelmingly, residents found the conference to be beneficial to the understanding of the four key contractual matters, with each topic having a statistically significant difference in perceived knowledge between the pre- and postconference questionnaires ( P < 0.001). The majority of the residents indicated that they wanted to learn more about business-of-medicine topics, in particular financial challenges (76%) and job opportunities (68%). Conclusions: Our results confirm that our curriculum is effective in increasing the residents' perceived understanding of restrictive covenants, malpractice insurance, negotiating skills, and job search. Our results also demonstrate that residents have a desire to learn more about job searches; negotiating skills; and contractual issues, including restrictive covenants and malpractice insurance. Abstract : Despite possible long-term repercussions, few training programs teach their residents about the business of medicine. In particular, certain contractual issues can adversely affect a young physician's career mobility. In this article, the authors describe a process in which we introduce residents in training to these important concepts.